Feather growth and quality across passerines is explained by breeding rather than moulting latitude - Horák, Kryštof; Bobek, Lukáš; Adámková, Marie; Kauzál, Ondřej; Kauzálová, Tereza; Manialeu, Judith Pouadjeu; Nguelefack, Télesphore Benoît; Nana, Eric Djomo; Jønsson, Knud Andreas; Munclinger, Pavel; Hořák, David; Sedláček, Ondřej; et al. (Proceedings. Biological sciences, 2022)
Tropical bird species are characterized by a comparatively slow pace of life, being predictably different from their temperate zone counterparts in their investments in growth, survival and reproduction. In birds, the development of functional plumage is often considered energetically demanding investment, with consequences on individual fitness and survival. However, current knowledge of interspecific variation in feather growth patterns is mostly based on species of the northern temperate zone. We evaluated patterns in tail feather growth rates (FGR) and feather quality (stress-induced fault bar occurrence; FBO), using 1518 individuals of 167 species and 39 passerine families inhabiting Afrotropical and northern temperate zones. We detected a clear difference in feather traits between species breeding in the temperate and tropical zones, with the latter having significantly slower FGR and three times higher FBO. Moreover, trans-Saharan latitudinal migrants resembled temperate zone residents in that they exhibited a comparatively fast FGR and low FBO, despite sharing moulting environments with tropical species. Our results reveal convergent latitudinal shifts in feather growth investments (latitudinal syndrome) across unrelated passerine families and underscore the importance of breeding latitude in determining cross-species variation in key avian life-history traits.
Keywords: Reproduction; fault bars; life-history; comparative analysis; Feathers; long-distance migration; Molting; pace-of-life syndromes; zvířata; Humans; Breeding; chov; shazování tělního pokryvu; Passeriformes; peří; rozmnožování; ptilochronology; lidé; Animals